Pengembangan Media Video Tutorial Pembuatan Macam-Macam Kampuh pada Mata Pelajaran Teknologi Menjahit Kelas X Tata Busana SMK Negeri 3 Kediri - Laillatul Arif Setyowati; Irma Russanti; Ec. Mein Kharnolis; Urip Wahyuningsih (Journal on Education, 2023)
This study is a development research to determine the level of feasibility by experts, namely material experts, media experts and linguists as well as to find out student responses to the video tutorial media for Making Various Kinds of Kampuh in the Class X Fashion Subject at SMK Negeri 3 Kediri. The research was developed using 4D model, namely define, design, develop and disseminate. The data collection method uses a media feasibility assessment questionnaire by Material Experts, Media Experts and Language Experts as well as student response questionnaires. The data analysis technique uses descriptive analysis techniques to process data from the validation results of media feasibility and student response data.The results of research and development of video tutorials for making various kinds of kampuh show the following results, (1) The feasibility level of the media by the Material Expert with an average score of 3.31 which is declared Very Feasible to be tested. The level of eligibility of the media by Media Experts with an average score of 3.73 which was declared Very Feasible to be tested. The feasibility level of the media by linguists with an average score of 3.50 which was declared Very Feasible to be tested. (2) The results of student responses in a small-scale trial with 6 people obtaining a score percentage of 89% are included in the Very Good category. While the results of student responses in the large-scale trial of 31 people obtained a score percentage of 92% included in the Very Good category.